Trenirovka sensornykh sistem kak dopolnitel'nyi faktor v povyshenii tekhnicheskogo masterstva gandbolistok - Katukov, Yu. V.; Prolomova, M. V. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
It was investigated which role the training of the sensoric system plays as additional factor in technic training of young female handball players. The results showed a positive effect of the special exercises applied in this experiment three times a week for 90 minutes each and directed to the visual and vestibular apparatus on the sport technique and the development of physical perfomance.